2005
DOI: 10.1111/j.1523-1755.2005.00303.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of preexisting vascular calcifications on mortality after renal transplantation

Abstract: VC evaluated by a simple and inexpensive plain radiography are an independent predictor of cardiovascular and all-cause mortality following RT. This finding may encourage the implementation of appropriate therapeutic strategies after RT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 26 publications
1
57
0
4
Order By: Relevance
“…Compared with the general population, KTRs are at a 3-to 5-fold higher risk (2), with some improvement in recent years (3). Calcification of the arterial wall is a strong cardiovascular risk factor in the general population (4-7), in patients on dialysis (8) and in KTRs (9,10). Arterial calcification is seen with aging and is known to proceed faster in patients with kidney disease (11)(12)(13), affecting >80% of KTRs (14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the general population, KTRs are at a 3-to 5-fold higher risk (2), with some improvement in recent years (3). Calcification of the arterial wall is a strong cardiovascular risk factor in the general population (4-7), in patients on dialysis (8) and in KTRs (9,10). Arterial calcification is seen with aging and is known to proceed faster in patients with kidney disease (11)(12)(13), affecting >80% of KTRs (14).…”
Section: Introductionmentioning
confidence: 99%
“…In aqueous solution, calcium and phosphate on supersaturation form amorphous nanoscale aggregates (Ca 6 [PO 4 ] 4 ), which are rapidly transformed to hydroxyapatite (Ca 10 [PO 4 ] 6 [OH] 2 ) (19,20). This mineral represents the main constituent of physiological (bone and teeth) and pathological (soft tissues and vasculature) calcifications.…”
Section: Introductionmentioning
confidence: 99%
“…Vascular calcification progresses substantially even in stable RTR and is an established predictor of morbidity and mortality. [3][4][5] The so-called traditional risk factors tobacco use, diabetes, obesity, hypertension, and dyslipidemia (i.e., the Framingham risk factors) have been identified as independent predictors of cardiovascular disease after kidney transplantation. 6 Biomineralization is a tightly regulated and location-specific process, determined by both inhibitors and promoters of calcification.…”
mentioning
confidence: 99%
“…At the time of renal transplantation the majority of ESRD patients already have an enormous burden of cardiovascular disease. Hernandez et al (2005) found pre-existing vascular calcification to be an independent predictor of cardiovascular and all-cause mortality following transplantation. Relapse of pre-existing or appearance new risk factors in the post-transplantation period result, in part, from the atherogenic potential of immunosuppressive drugs (Ojo 2006).…”
Section: Discussionmentioning
confidence: 94%